Structural and mechanical properties of organogels: Role of oil and gelator molecular structure - Cerqueira, Miguel Ângelo Parente Ribeiro (2017)
Supplementary data to this article can be found online at http://dx.doi.org/10.1016/j.foodres.2017.03.021.